Peran Media Sosial Instagram Dalam Mempromosikan Produk Ritel Pada PT. Iko Minang Ritel - Adhitya, Lucky; Putra, Tri Andi Eka; Ramadhani, Diva; Nugraha, Hafiz (Riset Sinergi Indonesia (RISINDO), 2025)
PT Iko Minang Ritel is a company that focuses on selling market products, to MSME products. In an ever-changing and competitive market industry, companies must innovate and understand market trends to remain relevant and competitive. One of the keys to their marketing strategy is social media. Currently the social media used by PT. Ikomart are Instagram, Facebook, WhatsApp. In today's rapidly developing digital era, the role of social media in the business world is very important in all aspects of the business sector, especially in the context of retail product marketing, has become increasingly significant. The influence of technology has become so dependent on the presence of the internet that it is easy to get information and also makes it easier to market a product. Brainstoring ideas is a discussion process to put forward ideas. Editorial planting is an activity where we put ideas that have been discussed into written form. Content production is an activity where we create content. Evaluation is measuring or assessing the quality, features, and also how the purpose for which the content was created. This evaluation will later be used to make decisions. With the social media Instagram, it can help companies promote more easily to many people because the majority of social media users currently are very large, especially Instagram users. So that the role of Instagram social media in carrying out promotions can increase sales and increase income for the company (9 pt).